2015
DOI: 10.11648/j.js.20150302.12
|View full text |Cite
|
Sign up to set email alerts
|

The Systematic Use of Fibrin-Based Biological Adhesive to Prevent Leakage Due to Healing Defects in Rectal Anastomosis Significantly Reduces Costs

Abstract: Abstract:Objective: To analyse hospital costs in the pre-, and intra-and post-operative periods associated with patients undergoing rectal resection with anastomosis, comparing the costs per patient with and without the use of fibrin-based biological adhesive(Tissucol Duo ® ). Methods: The cost analysis was designed with a subsample of 37 patients who underwent rectal anastomosis in a randomised, single-blind, controlled, parallel comparison between two groups, to evaluate the effectiveness of fibrin-based bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(15 reference statements)
2
5
0
Order By: Relevance
“…A significant difference in AL rates of 18.8% and 52.5% for fibrin sealant and controls, respectively, have previously been reported. 31 The revision rate input was also reported in this study, whereby revision surgery was required in 2 of 16 (12.5%) patients receiving Tisseel, and 9 of 21 (42.9%) patients that received no fibrin sealant to close the anastomoses. 31 Clinical outcomes that were not reported in the Oliver study were identified from other studies with a similar patient population.…”
Section: Clinical Inputssupporting
confidence: 75%
See 4 more Smart Citations
“…A significant difference in AL rates of 18.8% and 52.5% for fibrin sealant and controls, respectively, have previously been reported. 31 The revision rate input was also reported in this study, whereby revision surgery was required in 2 of 16 (12.5%) patients receiving Tisseel, and 9 of 21 (42.9%) patients that received no fibrin sealant to close the anastomoses. 31 Clinical outcomes that were not reported in the Oliver study were identified from other studies with a similar patient population.…”
Section: Clinical Inputssupporting
confidence: 75%
“…31 The revision rate input was also reported in this study, whereby revision surgery was required in 2 of 16 (12.5%) patients receiving Tisseel, and 9 of 21 (42.9%) patients that received no fibrin sealant to close the anastomoses. 31 Clinical outcomes that were not reported in the Oliver study were identified from other studies with a similar patient population. Hospitalization lengths of 9 days and 9.5 days for Tisseel versus the cohort that did not receive any fibrin sealant were found from the study by Kim et al 20,23 The study reported by Angelini et al reported estimates on bleeding during rectal surgeries which employ fibrin sealant (0.5%) vs no sealant (0.7%).…”
Section: Clinical Inputssupporting
confidence: 75%
See 3 more Smart Citations